2019
DOI: 10.2478/vzoo-2019-0018
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and Distribution of Naked Amoebae in Water Bodies of Sumy Region (Ukraine)

Abstract: Taxonomy of naked amoebae and specifics of their distribution in water bodies of Sumy Region are presented. Our research identified 12 species of naked amoebae of 11 morphotypes. We established their ecological groups relative to abiotic aquatic factors: euryoxidic, stenooxidic, stenobiotic and those that survive in a wide range of organic matter content. According to the species composition, swamp and riparian species complexes of naked amoebae were identified. It was found that species complexes of amoeba ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 8 publications
0
3
0
2
Order By: Relevance
“…During the period of research in 2013-2021 we identified 44 species of naked amoebae in freshwater water bodies, 23 species in soils, 13 species in epiphytic mosses and lichens and 10 species in epilithic habitats of Ukraine (Patsyuk, 2015(Patsyuk, , 2017(Patsyuk, , 2020Patsyuk et al, 2019). We can say that the amoebae of the fauna of water bodies, soils, epiphytes and epiliths of Ukraine are similar.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…During the period of research in 2013-2021 we identified 44 species of naked amoebae in freshwater water bodies, 23 species in soils, 13 species in epiphytic mosses and lichens and 10 species in epilithic habitats of Ukraine (Patsyuk, 2015(Patsyuk, , 2017(Patsyuk, , 2020Patsyuk et al, 2019). We can say that the amoebae of the fauna of water bodies, soils, epiphytes and epiliths of Ukraine are similar.…”
Section: Introductionmentioning
confidence: 93%
“…4. Locomotor forms of similis Page, referred Vexillifera sp (Patsyuk, 2013(Patsyuk, , 2020Patsyuk et al, 2019)…”
mentioning
confidence: 99%
“…Most marine and brackish water Vannella species were isolated only once, and never reisolated since their initial description, thus no data on their geographic distribution are available. There are few cases when a vannellid species was reported from geographically distant locations, but in all these studies they were identified based on morphology (Davis et al, 1978;Rogerson and Hauer, 2002;Patsyuk, 2016;Patsyuk and Onyshchuk, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Вивчення амеб в Україні стосувалося лише прісноводної фауни [12][13][14][15][16][17][18]. Даних щодо поширення цих протистів у наземних біотопах практично немає [19,20].…”
unclassified